In vitro regeneration of bamboo species - Lee, Pay Chiann; Muniandi, Sures Kumar; Ab Shukor, Nor Aini (Universiti Putra Malaysia Press, 2018)
This review paper discussed about journals related to micropropagation of bamboo species. In recent years, the application of tissue culture technique like in vitro micropropagation has been used to meet the demands for bamboo products. In the past 30 years, protocols for micropropagation of various bamboo species have been established by researchers from all over the world. The controlling factors for cultures such as the explants, culture medium, carbon sources, combination and concentration of plant growth regulators and other additional additives are varied amongst. The controlling factors are crucial in developing successful regeneration protocols for various bamboo species. This paper is attempted to review and summarize the available and up to date information regarding in vitro micropropagation of bamboos.